DESIGN OPTIMIZATION OF LAY-ON INSTRUMENT CAPACITOR - A. A. Jejora (Наука и техника)
The paper describes a development of a mathematical model for a lay-on instrument capacitor that takes into account an actual electrode thickness. Validity check of the mathematical model has been carried out in the paper. The paper contains quantitative evaluations and recommendations on design optimization of the lay-on instrument capacitor.